Frozen Section Diagnosis: Accuracy and Errors; with Emphasis on Reasons for Discordance - Gidwani, Roopam Kishore; Goswami, Falguni Jay; Mehta, Arpan; Shah, Nirali V; Prajapati, Shobhana Ashok; Shah, Manisha M (Annals of Pathology and Laboratory Medicine, 2021)
Background: Frozen section is a multistep process involving surgical resection, intraoperative preparation of slides and their microscopic examination. It is important to assess concordant, discordant and deferred diagnosis rates from intra-operative frozen section diagnosis with final diagnosis on paraffin section and to determine the reasons for discordance. An integral part of quality assurance in surgical pathology entails the correlation of intra-operative frozen section diagnosis with final diagnosis on permanent section. Methods: A retrospective analysis of 117 cases of frozen section biopsy was carried out which were reported in the Histopathology department between July 2007 to June 2012. The correlation between the frozen section diagnosis with final histological diagnosis was performed in order to check the accuracy of the technique. The number and type of discrepancies were compared, causes for the discrepancies were analyzed in order to decrease the avoidable errors and improve on the frozen section diagnoses. Results: The overall accuracy of frozen section diagnoses over 5years was 90.60% with false positive rate of 0.85%, false negative rate of 6.84% and 1.71% of deferred diagnosis. Sensitivity was 87.69% and Specificity was 98%. The discrepancies were mainly due to the interpretation error, sampling error and technical artefacts. Conclusions: Gross inspection, sampling by pathologist, frozen section complemented with cytological and histological review and cooperation between consultants can avoid certain limitations and provide rapid, reliable, cost effective information necessary for optimum patient care.